STRATEGI PUBLIC RELATIONS AFTERHOUR BILLIARD AND BAR DALAM MEMPERTAHANKAN EKSISTENSI - Anidya, Annisa (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2013)
The research was conducted in Afterhour Billiard and Bar is located at Sarinah Building Jl . MH . Thamrin inCentral Jakarta . The place is one of the pioneers of the birth of the entertainment industry who introduced thebilliard sport in Indonesia. Along perkembagan communication technology , making Afterhour as one example ofa growing industry and created competition . Competition has an impact on the company as a place of entertainmentpenurunaneksistensi playing billiard famous in Jakarta .The competition to be the research background . To deal with these problems required countermeasures correctlyso as not to have a serious impact on the company .This study raised the question of how to maintain the corporate existence , to address the problems that occurred .In an effort to maintain its existence , the specific strategies and tactics needed proper communication conductedby Public Relations . Therefore this research titled Strategic Public RelationsAfterhour Billiard and Bar Sarinahin Retaining existence .This study aims to determine what strategies are executed Public Relations Afterhour in maintaining customerloyalty ? . And what strategies are implemented as a marketing function that is run by the Public Relations .Qualitative method is chosen as the method of research as a strategy for loyalty can not be measured in numbersor other numerical computation . But can only be measured with words that describe assessment . This descriptivetype of research , so this writer will be able to describe with words that describe the research regarding thePublic Relations strategy .This research involves the theory of interpersonal communication , because communication is the most effectivecommunication and efficient to give effect to do so . The data collection method or information retrieval in-depthinterviews conducted with the informants that were the subject of this study in order to obtain actual information .The concept of this thesis research uses nine steps theory of public relations strategy which consists of nine steps, namely planning research situation analysis , organizational analysis , external analysis , goal setting and objects, determines communication action , designing effective communication , establish communication tactics ,implementation and evaluation plan .This research is expected to help clarify the Public Relations strategies and provide knowledge in the field of communication. it is also expected to be information for its readers .